Pelaksanaan Pengawasan Keimigrasian terhadap Warga Negara Asing yang Menggunakan Visa Kunjungan Wisata - Fadli Saputra (Faculty of Social Science, Universitas Negeri Padang, 2021)
Padang City is a city located in the province of West Sumatra, with a very strategic geographical condition, making the city of Padang rich in natural beauty. The beauty of nature is used by people in Padang City as a tourist spot, so that it is able to steal the attention of foreign tourists to come to visit, foreign tourists who enter and leave the Padang City area, all of which are under immigration control. Immigration is a form of enforcement in the implementation of state government sovereignty, therefore to facilitate immigration in carrying out its duties and functions in the supervision sector of foreign visits, a class 1 Padang Immigration office was formed. Since the enactment of Presidential Regulation Number 21 of 2016 regarding Visit Visas in Indonesia, it is clear that 169 countries are free to visit Padang City only with their passports. The purpose of this Presidential Regulation is to increase foreign tourist visits to Padang City so that it has an impact on increasing national development in general and increasing economy in particular, foreign tourists who come are expected to have a positive impact on the economy of the people of Padang City. However, the fact is not as imagined by the Padang City Government, the tourist visit permit granted to foreign tourists is prone to abuse, especially looking for work or opening business land and settling in a place. Researchers took the research location at the Padang Class I Immigration Office, because the city of Padang is one of the most attractive cities to be visited by foreign tourists, especially its natural beauty. As a government effort in order to support the maintenance of stability, security and vigilance against all negative impacts arising from the crossing of people between countries, and the activities of foreigners in Padang City, it is deemed necessary to carry out supervision of foreigners and immigration actions in a fast, thorough, and coordinated manner, without must ignore the openness in providing services to foreigners who are at the Class 1 Padang Immigration Office.